IMPACT OF POLITICS ON THE MANAGEMENT OF PUBLIC SECONDARY SCHOOLS IN ENUGU STATE - Onubuleze, Franklin Kelechi; Akpagu, Cletus I (Top Educational Review Journal (TERJ), 2020)
This study sought to examine the impact of politics on the management of public secondary schools in Enugu State. The design of the study was a descriptive survey. Two research questions and two null hypotheses guided the study. The population of the study was 311 made up of 65 principals and 246 teachers in the secondary schools in Enugu South L. G. A. There was no sampling because the population was manageable. Questionnaire was used for data collection. Mean with standard deviation was used to answer the research questions while t-test was used to test the hypotheses. Some findings of the study include; the fact that misappropriation of funds disrupt peace in schools, favoritism in the disbursement of funds leads to conflict in schools, funds meant for the payment of teachers salaries and allowances are often misappropriated and this result in industrial dispute. Among the recommendations includes the fact that schools should be organising workshops, public seminars and enlightenment programmes in their schools and community to educate people on the negative impact of politics and the way out.